Introduction: Global Economic Inclusion and African Workers. Issue 4 (2nd April 2016) - Meagher, Kate; Mann, Laura; Bolt, Maxim
Abstract: This introductory article explores the transformative potential of global connections for African workers. It challenges recent claims that African workers have become functionally irrelevant to the global economy by examining the shift of global demand for African workers from formal to increasingly informalised labour arrangements, mediated by social enterprises, labour brokers and graduate entrepreneurs. Focusing on global employment connections initiated from above and from below, we consider why global labour linkages have tended to increase rather than reduce problems of vulnerable and unstable working conditions within African countries, and consider the economic and political conditions needed for African workers to capture the gains of inclusion in the global economy.